2020
DOI: 10.1177/2055217319841881
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and phenotypes of multiple sclerosis in the Middle East North Africa (MENA) region

Abstract: The Middle East North Africa (MENA) region falls in the low-to-moderate multiple sclerosis (MS) prevalence zone, with prevalence rates slightly lower than Southern Europe but much higher than sub-Saharan Africa. However, there is clearly a trend toward increased MS prevalence over the last few decades, consistent with the globally rising prevalence of the disease. We analyzed all data collected from the MENACTRIMS (Middle East North Africa Committee for Treatment and Research in Multiple Sclerosis) registry by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
6
33
0
Order By: Relevance
“…The United States validated a case-ascertainment algorithm and reported an almost doubling of prevalent cases to 913,925 in 2019. 5 An increasing prevalence of MS has also been reported across the Middle East and North African region, 6 in the Russian Federation, 7 Canada, 8 Australia 9 and in several European countries (Denmark, Germany, Poland, the United Kingdom). The Global Burden of Disease (GBD) 2016 Multiple Sclerosis Collaborators similarly reported that the prevalence of MS had risen between 1990 and 2016, estimating that there were 2,221,188 (95% Uncertainty Interval 2,033,866–2,436,858) persons living with MS in 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States validated a case-ascertainment algorithm and reported an almost doubling of prevalent cases to 913,925 in 2019. 5 An increasing prevalence of MS has also been reported across the Middle East and North African region, 6 in the Russian Federation, 7 Canada, 8 Australia 9 and in several European countries (Denmark, Germany, Poland, the United Kingdom). The Global Burden of Disease (GBD) 2016 Multiple Sclerosis Collaborators similarly reported that the prevalence of MS had risen between 1990 and 2016, estimating that there were 2,221,188 (95% Uncertainty Interval 2,033,866–2,436,858) persons living with MS in 2016.…”
Section: Resultsmentioning
confidence: 99%
“…. 5 An increasing prevalence of MS has also been reported across the Middle East and North African region, 6 in the Russian Federation, 7 Canada, 10 The GBD group relied on information in the literature, and modelling to generate estimates, and the updated United States prevalence figures used in the present Atlas which showed an increase of over 400,000 Americans living with MS were not available at that time.…”
mentioning
confidence: 99%
“…Also, this nding could justify the high heterogeneity between studies, at least in part. Relevantly, other metaanalysis indicated different FMS prevalence in Iran (8.9%) [63] and the Middle East North Africa region (17.8%) [64].…”
Section: Discussionmentioning
confidence: 87%
“…(AlJumah et al, 2020) In Lebanon, Yamout and colleagues found a high female/ male ratio of approximately 3. (Yamout et al, 2020). A number of previous studies have reported that 0.4-5.6% of MS patients have their onset of symptoms before the age of 16.…”
Section: Resultsmentioning
confidence: 99%